(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
For more than a decade, the Mathematics Faculty of the National University of Rosario has been supporting volunteer and university extension projects to articulate work with schools in disadvantaged or vulnerable contexts in the city of Rosario and surrounding areas. This is done through the design, restoration, use and analysis of didactic resources, particularly for the teaching and learning of Mathematics. The resources considered have been both digital and physical, where access to them is often subject to ups and downs, with limitations of various kinds; including economic, cultural, disciplinary, pedagogical and socio-environmental ones. The peculiarity is that, for its elaboration, it seeks to use the ecological 3Rs (reduce, reuse, recycle) as a transversal contribution in accordance with the Sustainable Development Goals.